2001
DOI: 10.4049/jimmunol.166.5.3533
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide Synthase Type 2 in Acute Infection with Murine Cytomegalovirus

Abstract: Whether or not NO plays a critical role in murine CMV (MCMV) infection has yet to be elucidated. In this study, we examined the role of NO in acute infection with MCMV using NO synthase type 2 (NOS2)-deficient mice. NOS2−/− mice were more susceptible to lethal infection with MCMV than NOS2+/+ mice and generated a much higher peak virus titer in the salivary gland after acute infection. A moderate increase in the MCMV titer was also observed in other organs of NOS2−/− mice such as the spleen, lung, and liver. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 65 publications
(55 reference statements)
4
47
0
Order By: Relevance
“…In contrast, IL-12-induced inhibition of vesicular stomatitis virus in the CNS required neither TNF-␣ nor IFN-␥ but was dependent on NOS-1 (17,18). A recent study extended these findings by demonstrating that IFN-␥-inducible NOS-2 is crucial for eliminating murine cytomegalovirus (27). In the cerebellum of BDV-infected GF-IL-12 mice, we observed induction of TNF-␣, IFN-␥, and IL-1 as well as NOS-2 genes, while NOS-1 and NOS-3 transcripts remained at control levels.…”
Section: Vol 76 2002 Interactions Of Bdv and Il-12 In The Cns 12229supporting
confidence: 58%
“…In contrast, IL-12-induced inhibition of vesicular stomatitis virus in the CNS required neither TNF-␣ nor IFN-␥ but was dependent on NOS-1 (17,18). A recent study extended these findings by demonstrating that IFN-␥-inducible NOS-2 is crucial for eliminating murine cytomegalovirus (27). In the cerebellum of BDV-infected GF-IL-12 mice, we observed induction of TNF-␣, IFN-␥, and IL-1 as well as NOS-2 genes, while NOS-1 and NOS-3 transcripts remained at control levels.…”
Section: Vol 76 2002 Interactions Of Bdv and Il-12 In The Cns 12229supporting
confidence: 58%
“…5B). It has been reported that iNOS deficiency leads to increased replication of MCMV after long infection periods with low MOI in peritoneal exudate macrophages (48). We determined whether the defective NO production in Tyk2-deficient cells contributes to the increased replication of MCMV in our experimental system.…”
Section: Tyk2 Is Required For Mcmv-induced Production Of Nomentioning
confidence: 99%
“…It has been previously reported that NO plays an important role in MCMV infections in vivo (13,48). We therefore determined NO production in the supernatants of MCMVinfected macrophages derived from Tyk2 Ϫ/Ϫ and WT mice.…”
Section: Tyk2 Is Required For Mcmv-induced Production Of Nomentioning
confidence: 99%
“…18,19 PB monocytes and macrophages have been identified as host cells that support viral replication 11,16,17,[20][21][22][23] and latency 22,24,25 ; however, these cells also have been implicated in host defense. 20,23,[26][27][28] The differentiation-dependent susceptibility of monocytes and macrophages to MCMV infection 22,23 has led to a consensus view that nonpermissive monocytes may disseminate infection and differentiate into permissive mature cells upon entry into tissues. This pattern is similar to that proposed to explain viral reactivation from latency 29 and has been reinforced by the apparent central role of myelomonocytic lineage cells in HCMV infection [30][31][32] and latency.…”
Section: Introductionmentioning
confidence: 99%